ICT Adoption of the Ateneo de Manila University's Loyola School Faculty - Rodrigo, Ma. Mercedes T (Archīum Ateneo, 2003)
The Ateneo de Manila University is an institution of higher learning in Quezon City, Philippines. The study determined the level of computer experience of the faculty; the extent to which faculty use computers to teach, the extent to which they required students to use computers, the demographic profile of Early Adopters (EAs) and Mainstream Faculty (MFs), and their patterns of computer use. Data showed that that faculty adoption of technology was limited to the support of traditional teaching methods. Although the faculty made substantial to extensive personal and professional use of Windows, productivity tools, email, browsers, and online databases, they only required students to use word processors extensively. Data showed no significant difference between gender, rank, employment, and computer usage characteristics of the EAs and MFs. However, MFs tended to have higher educational attainments than EAs. MFs also began purchasing computers earlier and tended to own more computers than EAs.